Construction workers' training: contributions to a more effective prevention culture - Gonçalves, Jorge Augusto Gago (2016)
This article presents an analysis of the degree of training, knowledge and involvement of construction workers with safety at work. With the results obtained, we aim to structure a set of preventive measures, concerning training, so as to decrease the number of work accidents in construction. We have designed one questionnaire survey for construction workers and one for safety technicians and senior technicians who deliver safety in construction training. It has been shown that, in Portugal, the lack of training and information about safety at work translates into an insufficient concern with prevention, which boosts the number of work accidents in construction. Therefore, there is the pressing need for Portugal to legally define the skills of all workers involved in construction in relation to safety at work.